2002
DOI: 10.1080/10400435.2002.10132052
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Design of Augmentative and Alternative Technologies for Young Children

Abstract: If children with significant communication disabilities are to attain the power of language, literacy, and communication early in their development, they must have access to appropriate augmentative and alternative communication (AAC) systems. AAC technologies for young children should (a) be highly appealing, capturing, and sustaining of their interest; (b) be seamlessly integrated into all aspects of daily living; (c) provide access to the magical power of communication, language, and literacy; (d) be synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 47 publications
0
40
0
2
Order By: Relevance
“…In this study, limitations of technology were cited as adversely affecting outcomes. Research and development are needed (a) to improve the technology available to individuals who use AAC; (b) to design communication systems with reduced operational demands (Light, 1997;Light & Drager, 2002); and (c) to develop technology that can meet the needs of multi-lingual persons. This research must be consumer driven (Blackstone, Williams, & Joyce, 2002), because consumers are the best informants.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…In this study, limitations of technology were cited as adversely affecting outcomes. Research and development are needed (a) to improve the technology available to individuals who use AAC; (b) to design communication systems with reduced operational demands (Light, 1997;Light & Drager, 2002); and (c) to develop technology that can meet the needs of multi-lingual persons. This research must be consumer driven (Blackstone, Williams, & Joyce, 2002), because consumers are the best informants.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…The costs and benefits of these skills are well known. What is needed is a similar understanding of the costs and benefits of AAC technology (Drager et al, 2003;Light & Drager, 2002) so that individuals who use AAC can make informed decisions. The success of the participants in this study provides strong testimony to the powerful ways current AAC technology can be used.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of informal interviews conducted with parents of young children who used aided AAC systems, parents consistently reported that their children seldom sought out their aided AAC systems as they did their toys (Light & Drager, 2002). The parents reported that they had to provide significant encouragement for their children to use their aided systems.…”
mentioning
confidence: 95%
“…It seems reasonable to argue that early intervention is more likely to be effective if AAC systems are highly appealing to young children with complex communication needs (Light & Drager, 2002), and that these children stand to reap many benefits from such systems. First and foremost, they may be more likely to use AAC systems that are appealing.…”
mentioning
confidence: 97%
See 1 more Smart Citation